Small suspension-feeding amphipods play a pivotal role in carbon dynamics around offshore man-made structures. (June 2022) - Mavraki, Ninon; Coolen, Joop W.P.; Kapasakali, Danae-Athena; Degraer, Steven; Vanaverbeke, Jan; Beermann, Jan
Abstract: The establishment of artificial hard substrates (i.e. offshore wind farms and oil and gas platforms) on marine soft sediments increases the available habitat for invertebrate communities that would otherwise be restricted to natural hard bottoms. Suspension feeding invertebrates clear a significant amount of particles from the water column and release organic matter in the form of feces, influencing the basis of marine food webs and affecting surrounding environments. Artificial structures in the southern North Sea are dominated by a suspension-feeding crustacean in terms of abundance and sometimes even biomass: the amphipod Jassa herdmani . Animal densities of this tiny biofouler are known to exceed 1 million individuals per m 2 . Despite their small body sizes and their simple filter apparatus, we hypothesized that J. herdmani is a highly effective suspension feeder with a significant impact on neighboring communities due to its high abundances. In a feeding experiment, individuals of J. herdmani were provided with either an algal or an animal diet under two different temperature regimes. Clearance rates and fecal-pellet carbon (FPC) were measured. The results revealed high clearance rates and subsequent FPC, which were more pronounced at the higher temperature. Furthermore, clearance rates and FPC varied insignificantly with different food items. We further used the current findings for upscaling calculations to the total number of offshore windfarms and oil and gas platforms in the southern North Sea. Our calculations indicated that J. herdmani alone clears 0.33–4.71 km 3 water per year in the southern North Sea. At the same time, these amphipods release 255–547 tons of carbon per year by means of defecation, thus enriching the surrounding soft sediments with organic matter. Our study highlights that tiny amphipods can mediate indirect effects of man-made structures in the North Sea, which could have a profound impact on pelagic and benthic habitats. Highlights: Artificial structure introduction has profound effects for the marine ecosystem. Small abundant amphipods can cause big changes to the marine environment. Jassa herdmani clears up to 0.009% of the entire North Sea per year. J. herdmani increases organic matter deposition by 0.3–0.9% in the south North Sea.